2007
DOI: 10.1007/s00392-007-0569-x
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of autologous mononuclear bone marrow stem cells in patients with peripheral arterial disease (The TAM-PAD study)

Abstract: Combined intraarterial and intramuscular transplantation of autologous mononuclear bone marrow stem cells is a clinically feasible and minimally invasive therapeutic option for patients with severe chronic peripheral occlusive arterial disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
97
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 23 publications
3
97
0
Order By: Relevance
“…ABI on exercise (from 0.62±0.17 to 0.77±0.15, p=0.018), capillary-venous oxygen saturation (from 50±15 to 62±6%, p=0.027) and venous occlusion plethysmography (from 4.6±1.7 to 6.5±1.7 ml/100 ml tissue/min, p<0.05) exhibited significant improvements as well [61]. Finally, 13 subjects with chronic PAD staged Fontaine IIb received combined intra-arterial and intramuscular BMMNC transplantation [62]. After 2 months, the pain-free walking distance increased significantly by more than 300% (from 147±90 to 500±614 m, p=0.001).…”
Section: Bmmncsmentioning
confidence: 93%
See 4 more Smart Citations
“…ABI on exercise (from 0.62±0.17 to 0.77±0.15, p=0.018), capillary-venous oxygen saturation (from 50±15 to 62±6%, p=0.027) and venous occlusion plethysmography (from 4.6±1.7 to 6.5±1.7 ml/100 ml tissue/min, p<0.05) exhibited significant improvements as well [61]. Finally, 13 subjects with chronic PAD staged Fontaine IIb received combined intra-arterial and intramuscular BMMNC transplantation [62]. After 2 months, the pain-free walking distance increased significantly by more than 300% (from 147±90 to 500±614 m, p=0.001).…”
Section: Bmmncsmentioning
confidence: 93%
“…After 2 months, the pain-free walking distance increased significantly by more than 300% (from 147±90 to 500±614 m, p=0.001). ABI rose, both at rest (from 0.66±0.18 to 0.80±0.15, p=0.003) and on exercise (from 0.64±0.19 to 0.76±0.16, p=0.006) [62]. The authors also found significant improvements in capillary-venous oxygen saturation (from 56±14 to 63±5, p=0.021) and venous occlusion plethysmography (from 2.1±0.7 to 2.5±0.7, p=0.009).…”
Section: Bmmncsmentioning
confidence: 96%
See 3 more Smart Citations